Transpeople (Khon kham-phet) in Thailand: Transprejudice, exclusion, and the presumption of mental illness - Winter, Sam (2011)
Gender identity variance (a person's identification as belonging to a gender other than that into which he or she was allocated at birth) appears to be a crosscultural and trans-historical aspect of human diversity; people of gender variant identity have been present in many societies across many historical periods. In the past, such people were often mistakenly labelled as "hermaphrodites", even when their physiologies were indubitably male or female. In recent decades, gender-variant people in the West have come to be called transsexual, sometimes transgender, often more informally as "transpeople". © 2011 by Hong Kong University Press, HKU. All Rights Reserved.